The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2008
DOI: 10.1255/jnirs.818
|View full text |Cite
|
Sign up to set email alerts
|

Application of near Infrared Spectroscopy for Estimating Wood Mechanical Properties of Small Clear and Full Length Lumber Specimens

Abstract: Most of the important wood properties are highly variable among species and individuals, and even in the same stem. 1 this variation in wood properties is recognised as one of the greatest problems facing the wood industry, where rapid costeffective methods for measuring the properties are required to segregate log and lumber materials for appropriate end products. traditional methods employed to measure wood characteristics are time-consuming, expensive and often destructive. thus, several attempts have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
1
4

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(81 citation statements)
references
References 29 publications
6
70
1
4
Order By: Relevance
“…However, in order to allow an easy comparison between our models as well as with the ones of the literature, we choose to keep nine as the number of components for the temperature-specific models and 16 for the generalized models. These numbers are comparable to the ones used in other studies on wood moisture content and basic density estimation: 8 (Hoffmeyer and Pedersen 1995, Defo et al 2007, Fujimoto et al 20089 (Thygesen andLundqvist 2000a, Mora et al 2011);10 (Thygesen and Lundqvist 2000a); and 14 (Defo et al 2007).…”
Section: Multivariate Data Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…However, in order to allow an easy comparison between our models as well as with the ones of the literature, we choose to keep nine as the number of components for the temperature-specific models and 16 for the generalized models. These numbers are comparable to the ones used in other studies on wood moisture content and basic density estimation: 8 (Hoffmeyer and Pedersen 1995, Defo et al 2007, Fujimoto et al 20089 (Thygesen andLundqvist 2000a, Mora et al 2011);10 (Thygesen and Lundqvist 2000a); and 14 (Defo et al 2007).…”
Section: Multivariate Data Analysissupporting
confidence: 84%
“…This is consistent with the results of Defo et al (2007) and can be explained by a higher roughness of the transversal section than the tangential section. Moreover, the cut ends of the lumens of the tracheids are exposed to the NIR incident radiation when scanning the transversal section of the wood and as a result, the NIR energy can travel further into the wood and is more absorbed (Fujimoto et al 2008). By contrast, when scanning the tangential section, it is the cell wall of the tracheid which is exposed to the NIR incident radiation resulting in a lower absorbance.…”
Section: Resultsmentioning
confidence: 99%
“…Fujimoto et al (2008) used spectral information from tangential (R² between 0.61 and 0.84) and radial (R² between 0.73 and 0.89) faces to estimate mechanical properties of two species of genus Larix and concluded that both spectra present the same overall tendency as to calibration. It should be noted that in this particular work calibrations for mechanical properties were based on a small number of samples (n), and also that new studies should be undertaken to investigate the influence of Estimation of the mechanical properties of wood ... spectra depending on the face measured, preferably with a larger number of samples and ensuring grain orientation is well defined throughout.…”
Section: Calibration Of Mechanical Properties Of Woodmentioning
confidence: 99%
“…Several works have demonstrated the use potential of near infrared spectroscopy to determine wood properties, as, for example, studies developed by Fujimoto et al (2008) and Schimleck et al (1999) into density and also into strength and stiffness properties. Viana et al (2009), by using NIRS technique for predicting the morfological characteristics and basic density, found interesting results.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many papers have demonstrated that NIR models present good performance in cross-validations or independent validations for wood density (Via et al, 2003(Via et al, , 2005Cogdill et al, 2004;Mora et al, 2008;Hein et al, 2009), mechanical properties (Schimleck et al, 2001;Kelley et al, 2004;Fujimoto et al, 2008) and chemical composition (Gierlinger et al, 2002;Kelley et al, 2004;Rodrigues et al, 2006;Sousa-Correia et al, 2007), there is still a lack for applications in real situations. While a number of studies have demonstrated that the NIR spectroscopy and multivariate analysis works well in laboratories where the conditions are controlled, limited studies have been done simulating in real industrial conditions, like pulp mills or wood processing factories.…”
Section: Accuracy Of Nir Technology For Predicting Wood Properties Inmentioning
confidence: 99%